Analisis Hubungan Perilaku Pro-Lingkungan dengan Besarnya Food Loss & Food Waste Berdasarkan MFCA - Rivanty, Nathania Ester; Hermawan, Ancella Anitawati (Jurnal Informatika Ekonomi Bisnis, 2024)
The volume of organic waste in East Jakarta continues to increase every year compared to other Jakarta areas. Food loss and food waste are generated from the food & beverage industry such as cafes and dominate the amount of organic waste in East Jakarta. Based on initial interviews, cafe’s management does not have a sense of urgency and believes that waste management will only increase costs. Cafes do not have standards for material usage so that a lot of waste generated from cafe operations. This study aims to analyze the relationship of pro-environmental behavior with food loss and food waste from the operations of four cafes in East Jakarta. The calculation of food loss and food waste is analyzed using material flow cost accounting (MFCA). The theory of pro-environmental behavior is used to explore management behavior in everyday life. Management understanding influences cafe operations by applying management habits to cafe operations. This research strategy is a case study, using observations, interviews, and data on cafe expenses for a week. This research uses descriptive quantitative, content, thematic, and constant comparative analysis. From the analysis, it was found that food loss and food waste in four cafes amounted to 7%-9% and that cafe management that does not have pro-environmental behavior has an influence on the amount of food loss and food waste when compared to management that is pro-environment. This explains that cafe management that does not have pro-environmental behavior has an influence on the amount of food loss and food waste when compared to managers or owners who have pro-environmental behavior.